Brief report: Validity and reliability of the Nigerian Autism Screening Questionnaire. (August 2022) - Bakare, Muideen O; Frazier, Thomas W; Karpur, Arun; Abubakar, Amina; Nyongesa, Moses Kachama; Mwangi, Paul Murimu; Dixon, Pamela; Khaliq, Izma; Gase, Natalie K; Sandstrom, Jonathan; Okidegbe, Nwanze; Rosanoff, Michael; et al.
Informant-report measures for screening symptoms of autism spectrum disorder (ASD) and other neurodevelopmental disorders (NDDs) are needed for low-resource settings if early identification is to be prioritized because early developmental concerns are likely to be expressed by parents and other caregivers. This paper describes the initial psychometric evaluation of the Nigeria Autism Screening Questionnaire (NASQ). Parents and other caregivers completed the NASQ on 12, 311 children ages 1 to 18 in a Nigerian population sample as part of the World Bank National General Household Survey conducted in the country in 2016. Factor analyses indicated a parsimonious three-factor structure with social communication/interaction, repetitive sensory motor, and insistence on sameness dimensions. Measurement invariance was excellent across age and sex. Reliability of the subscales and total scale was good, and item response theory analyses indicated good measurement precision in the range from below average to high scores, crucial for screening, and tracking ASD symptoms. Studies with gold standard ASD diagnostic instruments and clinical confirmation are needed to evaluate screening and diagnostic accuracy. The NASQ appears to be a reliable instrument with a clear factor structure and potential for use in screening and tracking ASD symptoms in future Nigerian samples. Lay abstract: Early intervention for individuals with autism spectrum disorder (ASD) is dependent on reliable methods for early detection. Screening for ASD symptoms is an important strategy in low- and middle-income countries that often lack adequate service infrastructure. This study aims to conduct preliminary evaluation of the psychometric properties of a tool developed and deployed in Nigeria called the Nigerian Autism Screening Questionnaire (NASQ). Results demonstrated that NASQ, when used as a community-based survey, has a clear factor structure with consistent measurement across age and sex, and that scores from below average to well above average are measured reliably. Future research is needed to examine the performance of this tool against confirmatory ASD diagnosis in screening and diagnostic contexts to further understand the utility and applicability of this tool in the resource-limited Nigerian setting.